Male farmers with mental health disorders: A scoping review. (6th February 2013) - Roy, Philippe; Tremblay, Gilles; Oliffe, John L.; Jbilou, Jalila; Robertson, Steve
Abstract The issue of male farmers' mental health raises many concerns including high rates of psychological distress and suicide amid the poor uptake of health services among this subgroup. Gender is an important social determinant of health, and this paper provides an overview of connections between farming and masculinities in the context of men's mental health disorders. This scoping review summarises findings drawn from 46 studies to discuss male farmers' mental health disorders, psychosocial interventions and barriers to help‐seeking. In providing the review, recommendations are made including the need for an array of study and intervention approaches to advance the mental health and well‐being of male farmers and their families.